2013
DOI: 10.2522/ptj.20120181
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise for Patients Undergoing Hematopoietic Stem Cell Transplantation: Systematic Review and Meta-Analyses of Randomized Controlled Trials

Abstract: The results suggest that recipients of HSCT may benefit from physical exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 38 publications
5
124
0
1
Order By: Relevance
“…Fourteen systematic reviews found an improvement in qol for patients with cancer participating in an exercise intervention during the active treatment or post-treatment period 11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Fourteen systematic reviews found an improvement in qol for patients with cancer participating in an exercise intervention during the active treatment or post-treatment period 11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…[45] This review found six trials conducted in patients with hematological malignances undergoing hematopoietic stem cell transplant (HSCT) and high dose chemotherapy, and only one trial [35] conducted in cancer patients with advanced disease. Muscle wasting is a common symptom, reported in more than 60 % of patients with advanced cancer [14] and patients with hematological malignancies undergoing stem cell transplants [46]. For both groups there is a need for treatment strategies that contribute to reduce side-effect of treatment, maintain muscle mass and strength in order to maintain quality of life, and prolong survival.…”
Section: Populationsmentioning
confidence: 99%
“…In other cancer populations, such as breast and prostate cancer, there is a large body of strong evidence supporting the efficacy of exercise training [6]. Specifically in alloBMT, there is a relatively small number of studies to date [7], although these also suggest that structured exercise training is safe and may be associated with improvements in fatigue and HRQoL [7]. The majority of studies have focused on structured exercise training, including a combination of aerobic and resistance training, following completion of BMT [7].…”
Section: Letter To Editormentioning
confidence: 99%
“…Specifically in alloBMT, there is a relatively small number of studies to date [7], although these also suggest that structured exercise training is safe and may be associated with improvements in fatigue and HRQoL [7]. The majority of studies have focused on structured exercise training, including a combination of aerobic and resistance training, following completion of BMT [7]. We believe there is a need to extend the scope of exercise delivery to focus on 1) a broader perspective of physical activity behaviour and 2) widen the delivery of exercise intervention to commence as early as possible pre-BMT and continue both during and after hospitalisation.…”
Section: Letter To Editormentioning
confidence: 99%